Software and Resources of Modern Programming Languages for Bioinformatics and Computational Vaccinology Research of the New Coronavirus Infection - M. V. Sprindzuk; A. S. Vladyko; L. P. Titov; A. P. Konchits (Цифровая трансформация)
The review paper focuses on the application of software for the purposes of genomics, immunoinformatics, computational vaccinology, mathematical epidemiology and phylogeny of the new coronavirus infection. Authors provide a classification of software for the investigation of COVID-19.